MCF-7 Resistant Doxorubicin are Characterized by Lamelapodia, Strong Adhesion on Substrate and P-gp Overexpression - Putri, Dyaningtyas Dewi P.; Sarmoko, .; Febriansah, Rifki; Puspitasari, Endah; Ismiyati, Nur; Fitriasari, Aditya (Indonesian Journal of Cancer Chemoprevention, 2011)
The  prognosis  of  breast  cancer  patients  is  closely  associated  with  the  response  of tumor  cells  to  chemotherapy  agent.  Doxorubicin  is  one  of  the  primary  chemotherapeutic agents  used  for  the  treatment  of  breast  cancer.  Resistance  to  chemotherapy  is  believed  to cause  treatment  failure  in  cancer  patients.  Furthermore,  long  time  exposure  to chemotherapeutic  agent  induces  cancer  cells  resistance.  MCF-7  sensitive  cells  used  as chemoresistance  model  have  overexpression  P-gp  (P-glycoprotein).  Chemoresistance  was established by treating MCF-7 cells with 0.5 µg/ml doxorubicin-contained medium for a week. 50% inhibiting concentration (IC50) doxorubicin on MCF-7 cells/DOX were determined using MTT assay. Western blot assay and immunocytochemistry assay was performed to determine the expression of P-gp. Morphological of MCF-7 cell/DOX was changing to become larger and have  lamellapodia.  IC50  value  of  doxorubicin  was  700  nM  on  MCF-7/DOX  and  400  nM  on sensitive MCF-7 cells. The MCF-7/DOX sensitivity to doxorubicin was decreased, shown by 1.5  fold  higher  IC50  of  doxorubicin  on  MCF-7/DOX  compared  to  MCF-7  sensitive  cells. Treatment doxorubicin to sensitive MCF-7 cells leads to the increasing P-gp expression. The P-gp  level  expression  has  strong  correlation  with  the  low  sensitivity  of  MCF-7/DOX  to doxorubicin.Key words: doxorubicin, resistance cells, sensitive MCF-7 cell